Subclavian steal syndrome associated with right aortic arch: A case report - Cai, Jing; Xie, Chao; Wang, Xianwei (Frontiers in Surgery, 2023)
The right aortic arch (RAA) is a rare congenital vascular variant disease. We reported a case of subclavian steal syndrome associated with RAA. The primary clinical symptoms were vertigo and ischemic symptoms of the left upper extremity. We diagnosed the condition using aortic computed tomography angiography and digital subtraction angiography. The patient underwent carotid-subclavian bypass surgery.